Alternative amendment for vineyards from by-products of pyro-bituminous shale: Effect on wine amino acids and biogenic amines. (November 2017) - Alañón, M.E.; Schumacher, R.; Díaz-Maroto, M.C.; Gómez-Alonso, S.; Pérez-Coello, M.S.
Abstract: With the aim of looking for a model of agroecological production, the use of by-products from pyro-bituminous shale as amendment, and its effect on wine amino acids and biogenic amines has been evaluated. Field trials aimed to compare the effect of different doses of conventional and limestone shale from by-products of pyro-bituminous. Four replicates for six different fertilization treatments were arranged in a split plot design during 2009/2010 and 2010/2011 vintage. A chromatographic analysis was carried out to evaluate the impact of fertilization treatments on the amino acid and biogenic amine content of wines produced. Results showed few significant differences among fertilization treatments tested according to the amino acids composition of wines, although it seemed that a combination of conventional and pyro-bituminous shale could be the best option. By-products of pyro-bituminous shale seem to be a good partial substitutive amendment for Brazilian vineyards. This research seems to be a new approach for sustainable revalorization of domestic fertilizers to enable minor environmental impacts and lower production costs without detriment to quality. Graphical abstract: Highlights: By-products of pyro-bituminous shale could be as alternative amendment. Amino acid and biogenic amine content were influenced by amendment treatments. Conventional and by-products of pyro-bituminous combined gave better results.